The Role of Multi-Stakeholder Partnership in Humanitarian Diplomacy in the Seroja Storm Event in East Nusa Tenggara 2021 - Nadia M Lobangpali; Christian H.J de Fretes; Putri Hergianasari (International Journal Labs, 2023)
This paper analyzes the role of multi-stakeholders in humanitarian diplomacy in the East Nusa Tenggara Seroja Storm event. This paper is analyzed using the concept of multistakeholder partnership, the concept of humanitarian diplomacy and the theory of liberalism. The selection of both concepts and one theory is described by the Seroja storm event as an event that causes serious impacts on human life which is closely related to the concepts and theories used as analysis knives. This research uses descriptive qualitative methods or literature studies. The purpose of the study is to explain to the readers about the issue of seroja which is the first natural disaster experienced by the people of Indonesia, and to explain the diplomatic steps taken by the government and the community in responding to the natural disaster experienced by the Indonesian people in the East Nusa Tenggara region. Based on the results of the study, it can be said that the Indonesian government, especially the NTT provincial disaster management agency and the community and volunteers affiliated to the FPRB have carried out appropriate coordination to help disaster victims. Coordination is rare to be important from the actions of the two institutions that have saved the people of NTT from serious impacts that reduce their rights. Successful efforts and roles are carried out in evacuating casualties, missing victims, injured, supplying food and sanitation needs, making evacuations, carrying out rehabilitation and reconstruction.